Effects of physical exercise on non-suicidal self-injury in adolescents: the chain mediating role of perceived social support and self-concept - Yu, Haoran; Mu, Qinglei; Li, Ke (Frontiers in Psychiatry, 2023)
Objective: To study the effect of physical exercise on non-suicidal self-injury in adolescents and to verify the chain mediating role of perceived social support and self-concept. Methods: A survey study was conducted on 1426 adolescents in Chengdu, Sichuan Province. A chain mediation model was used to verify whether perceived social support and self-concept played a mediating role. Results: Physical exercise was significantly negatively associated with non-suicidal self-injury in adolescents (β = -0.53, P < 0.01) and significantly positively associated with perceived social support and selfconcept (β = 0.52, 0.54, P < 0.01), and perceived social support and self-concept were significantly negatively associated with non-suicidal self-injury (β = -0.59, P < 0.01; β = -0.64, P < 0.01), and perceived social support was able to significantly and positively associate self-concept (β = 0.76, P < 0.01).Conclusion: Perceived social support and self-concept play a chain mediating role in the effect of physical exercise on non-suicidal self-injury in adolescents, and it is recommended that the development of perceived social support and self-concept be emphasized during adolescents' development, which has the potential to reduce the incidence of non-suicidal self-injurious behaviors in adolescents.